1997
DOI: 10.1080/03014223.1997.9518121
|View full text |Cite
|
Sign up to set email alerts
|

Activity and food intake of captivePlacostylus fibratus(Gastropoda: Bulimulidae) in New Caledonia

Abstract: Placostylus fibratus is an endemic endangered species from New Caledonia. This snail is favoured as food, and the harvests for consumption from the wild population increase alarmingly. Thus, local authorities decided to promote research into the rearing methods for P. fibratus. Sixty-three snails from the Isle of Pines, divided into five groups, were subjected to different temperatures (20, 25, and 30°C) and humidities (80 ± 5% and 95 ± 5%) and constant light conditions (12 h:12 h photoperiod). The variables m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Many of the New Caledonian taxa are threatened (Neubert 2001) and some are still used for food. Salas et al (1997) provide some data on the biology of P. fibratus.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the New Caledonian taxa are threatened (Neubert 2001) and some are still used for food. Salas et al (1997) provide some data on the biology of P. fibratus.…”
Section: Introductionmentioning
confidence: 99%
“…Many Placostylus species are considered to be at risk of extinction (IUCN Species Survival Commission 2003). Threats include clearing of habitat, predation by introduced vertebrate species such as rodents, pigs and Eurasian thrushes (Parrish et al 1995;Sherley et al 1998) and, in some areas, overharvesting of wild snails for human consumption (Salas et al 1997). New Caledonian Placostylus species were recently described in the popular print media as rare but much-loved when simmered in white wine and garlic (Guy 2004).…”
Section: Placostylus Bivaricosusmentioning
confidence: 99%
“…Placostylus bivaricosus is generally active at night. Nocturnal behaviour in the related New Caledonian species Placostylus fibratus was found to be related to a preference for lower temperatures and higher humidity levels (Salas et al 1997). Placostylus species are unable to seal the shell aperture during dry conditions and are therefore prone to desiccation (Sherley 1994).…”
Section: Placostylus Bivaricosusmentioning
confidence: 99%
“…Again, P. augusta hatchling growth rates in captivity contradict this finding, suggesting that during the study period, the hatchling snails were not thriving in the captive environment. Studies of early rearing efforts for the land snail Placostylus fibratus also reported a very slow growth rate for captive juveniles (Salas et al 1997). However, through many years of adaptive management, with changes to substrate, light and diet (including calcium supplementation), growth rates in captivity have now been accelerated (Brescia et al 2008).…”
Section: Growth Ratesmentioning
confidence: 99%
“…Early efforts to breed Placostylus snails successfully in New Zealand and New Caledonia were also wrought with difficulty (Salas et al 1997;Stringer & Parrish 2003. However, following many years of monitoring and refining captive management methods, Placostylus fibratus have now been successfully captive-bred for large-scale reintroductions (Brescia et al 2008).…”
Section: Introductionmentioning
confidence: 99%